PHYTOCHEMICAL AND ANTIMICROBIAL EVALUATION OF SUBSTANCES IN THE BIGNONIACEAE FAMILY - Gomes Krause, Naiely; Caldas Fagundes Serrano, Catarina; Karolini Walger Schultz, Leticia (Journal of Interdisciplinary Debates, 2022)
The ipê belongs to the Bignoniaceae Family, which has approximately 120 genera and 800 species, the largest genus belonging to this family is Tabebuia, found with great diversity in South America, due to its tropical and subtropical climate. Due to the enormous variety of plants of this genus, it was necessary to create a division based on their specific characteristics: Tabebuia, Handroanthus (exclusive to represent the species existing in Brazil) and Roseodendron. This work sought to gather information on the antimicrobial and phytochemical activity of substances found in the Bignoniaceae family, respectively, in the genera: Tabebuia rosea-ipê rosa; Handroanthus impetiginosus- purple ipe; Handroanthus albus-ipe yellow; Tabebuia roseo-alba-ipê (white) through the extraction of lapachol. With the present study, it is possible to evidence the great benefits arising from the extracts of ipês. However, the scarcity of studies of this type is clear, this fact makes it difficult to disseminate proof of the beneficial effects of ipês.